Design, optimization, and evaluation of hydrogel of primaquine loaded nanoemulsion for malaria therapy - Pankaj Sharma; Mukul Tailang (Future Journal of Pharmaceutical Sciences, 2020)
Abstract Background The present study aimed to design, optimize, and evaluate primaquine loaded nanoemulgel for malaria treatment. Nanoemulgel was prepared with the help of different components such as castor oil, Tween 80:Transcutol P (S mix ratio), and polymers. Pseudoternary phase diagram was constructed to optimize S mix ratio. Response surface methodology was used for the optimization of nanoemulsion preparation based on characterization parameters such as droplet size (nm), zeta potential (mv), polydispersity index (PDI), viscosity (mPa·S), conductivity (mS/cm), and percent drug release. Based on these parameter results, F5 formulation was selected as an optimized formulation. F5 formulation was loaded in hydrogel preparation which was developed by using hydroxypropyl methylcellulose (HPMC K15M) 1-2% concentrations. The prepared nanoemulgel was evaluated with the following parameters: percent drug content, in vitro drug release, ex vivo skin permeation, pH determination, spreadability determination, and viscosity measurement. Results The droplets of primaquine loaded nanoemulsion were nanosized (10–200 nm) in the transmission electron microscope (TEM) images. Zeta potential for all formulations (F1-F9) was observed as − 0.7 ± 0.02 to 2.12 ± 0.04 mv. Response surface curves were plotted for optimization of perfect nanoemulsion preparation. Nanoemulgels (F5, F5a, F5b, and F5c) were evaluated for their different parameters such as pH (F5, 5.2 ± 0.2; F5a, 5.3 ± 0.1; F5b, 5.3 ± 0.1; and F5c, 5.4 ± 0.1), viscosity (mPa·S) (F5, 9876 ± 0.61; F5a, 14,564.6 ± 0.42; F5b, 14,841.9 ± 0.82; and F5c, 16,872.1 ± 0.921), spreadability (g.cm/s) (F5, 7.89 ± 0.10; F5a, 5.09 ± 0.03; F5b, 4.30 ± 0.02; and F5c, 3.13 ± 0.01), and percent drug content (F5, 100 ± 0.46; F5a, 98.10 ± 0.38; F5b, 99.70 ± 0.41; and F5c, 97.34 ± 0.51), and ex vivo skin flux of F5b was evaluated for 24 h. Ex vivo skin permeability was found ~ 70% within 12 h and ~ 86% within 24 h. Conclusion The nanoemulsion loaded hydrogel of primaquine with optimum viscosity was prepared for transdermal application. Nanoemulgel was prepared by using HPMC K15M into nanoemulsion because HPMC K15M was responsible for significant viscosity. The permeation rate of nanoemulgel was greater than other drug solutions. The great permeation rate was achieved by the incorporation of Transcutol P (cosurfactant). The optimized formulation was justified by using statistics. Stability studies confirmed that nanoemulgel is a promising carrier for the delivery of primaquine.